Use of grape seed extract and its implications in the skin aging process (Research, Society and Development, 2022)
Skin aging is a complex process and not fully elucidated in the literature, although it is known that its changes are influenced by intrinsic and extrinsic factors, such as ultraviolet radiation (UV) and changes in the extracellular matrix. Given this context, therapeutic interventions based on grape seed extract arise, as it is an abundant source of polyphenols, alkaloids, steroids, cardiac glycosides, saponins and large amounts of Resveratrol. Thus, the present research sought to describe the benefits of using grape seed extract in the fight against aging. Where used as a methodology bibliographic research of the integrative review type in the databases of the Virtual Health Library, using the insertion of DeCS: Grape Seed Extract (Grape Seed Extract), Skin Aging/Skin Aging/ Envejecimiento de la Piel, combined with the Boolean operator AND to perform the searches. Articles that had full text available for reading and that had used formulations with grape seed extract in order to promote anti-aging effects on the skin were included. Duplicates and bibliographic searches are excluded. The results of this review found that the use of grape seed extracts used in research showed positive outcomes in terms of their anti-aging activity, as evidenced by reduced pH, wrinkles, dark circles, redness, and skin blemishes. Concluding that formulations that use grape seed extract benefit from its properties to promote a healthier microenvironment in the skin.